Oleuropein enhances proteasomal activity and reduces mutant huntingtin-induced cytotoxicity - Huang, Zih-Ning; Lee, Sin-Yi; Chen, Jie-Mao; Huang, Zih-Ting; Her, Lu-Shiun (Frontiers in Pharmacology, 2024)
Introduction Huntington’s disease (HD) is a hereditary neurodegenerative disorder that primarily affects the striatum, a brain region responsible for movement control. The disease is characterized by the mutant huntingtin (mHtt) proteins with an extended polyQ stretch, which are prone to aggregation. These mHtt aggregates accumulate in neurons and are the primary cause of the neuropathology associated with HD. To date, no effective cure for HD has been developed. Methods The immortalized STHdhQ111/Q111 striatal cell line, the mHtt-transfected wild-type STHdhQ7/Q7 striatal cell line, and N2a cells were used as Huntington's disease cell models. Flow cytometry was used to assess cellular reactive oxygen species and transfection efficiency. The CCK-8 assay was used to measure cell viability, while fluorescence microscopy was used to quantify aggregates. Immunoblotting analyses were used to evaluate the effects on protein expression. Results Polyphenols are natural antioxidants that offer neuroprotection in neurological disorders. In this study, we provide evidence that oleuropein, the primary polyphenol in olive leaves and olive oil, enhances cell viability in HD cell models, including. STHdhQ7/Q7STHdhQ7/Q7 striatal cells, N2a cells ectopically expressing the truncated mHtt, and STHdhQ111/Q111 striatal cells expressing the full-length mHtt. Oleuropein effectively reduced both soluble and aggregated forms of mHtt protein in these HD model cells. Notably, the reduction of mHtt aggregates associated with oleuropein was linked to increased proteasome activity rather than changes in autophagic flux. Oleuropein seems to modulate proteasome activity through an unidentified pathway, as it did not affect the 20S proteasome catalytic β subunits, the proteasome regulator PA28γ, or multiple MAPK pathways. Discussion We demonstrated that oleuropein enhances the degradation of mHtt by increasing proteasomal protease activities and alleviates mHtt-induced cytotoxicity. Hence, we propose that oleuropein and potentially other polyphenols hold promise as a candidate for alleviating Huntington's disease.